Digitalization of Higher Education Administration through a Paperless Platform to Improve AIK Lecturer Performance at Universitas Muhammadiyah Pontianak (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This study develops a web-based digital platform to improve administrative efficiency in Al-Islam and Kemuhammadiyahan (AIK) courses at Universitas Muhammadiyah Pontianak. Using a participatory development approach, the system integrates digital attendance, paperless module distribution, recitation assessment, and real-time reporting. Usability evaluation based on the Technology Acceptance Model showed high perceived ease of use (4.37/5.00) and usefulness (4.51/5.00). The platform eliminated paper-based processes, reduced reporting time from several weeks to real-time, and lowered operational costs. These findings demonstrate that integrated digital platforms significantly enhance administrative efficiency in higher education.